The effect of standards and fuel prices on automobile fuel economy: an international analysis - Zachariadis, Theodoros; Clerides, Sofronis (My University, 2008)
There is an intense debate over whether fuel economy standards or fuel taxation is the more efficient policy instrument to raise fuel economy and reduce CO 2 emissions of cars. The aim of this paper is to analyze the impact of standards and fuel prices on new-car fuel economy with the aid of cross-section time series analysis of data from 18 countries. We employ a dynamic specification of new-car fuel consumption as a function of fuel prices, standards and per capita income. It turns out that standards have induced considerable fuel savings throughout the world, although their welfare impact is not examined here. If standards are not further tightened then retail fuel prices would have to remain at high levels for more than a decade in order to attain similar fuel savings. Finally, without higher fuel prices or tighter standards, one should not expect any marked improvements in fuel economy under 'business as usual' conditions.
Keywords: Motor fuels--Taxation; Greenhouse gases; Energy policy; Automobiles--Pollution control devices